2010
DOI: 10.1097/pcc.0b013e3181a64743
|View full text |Cite
|
Sign up to set email alerts
|

Adrenocortical response in infants undergoing cardiac surgery with cardiopulmonary bypass and circulatory arrest*

Abstract: The majority of infants with congenital heart disease and intact hypothalamic-pituitary-adrenal axes demonstrated an appropriate adrenocortical stress response to cardiac surgery. Peak serum cortisol was unrelated to CPB/DHCA time and did not predict the level of inotrope support. However, a subset of patients with elevated ACTH/cortisol ratios seemed to have a clinical status consistent with adrenal insufficiency and may be a target group for early postoperative steroid therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
53
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(59 citation statements)
references
References 20 publications
5
53
1
Order By: Relevance
“…Surgical trauma may induce the stress response, which stimulates the production of many endogenous substances involved in perioperative myocardial ischemia (17,18). The stress response may lead to a series of adverse effects such as the inhibition of organ function, a decline in immune function and metabolic enhancement (17,18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Surgical trauma may induce the stress response, which stimulates the production of many endogenous substances involved in perioperative myocardial ischemia (17,18). The stress response may lead to a series of adverse effects such as the inhibition of organ function, a decline in immune function and metabolic enhancement (17,18).…”
Section: Discussionmentioning
confidence: 99%
“…The stress response may lead to a series of adverse effects such as the inhibition of organ function, a decline in immune function and metabolic enhancement (17,18). It has been demonstrated that general anesthesia alone is unable to effectively suppress the surgical stress response (8).…”
Section: Discussionmentioning
confidence: 99%
“…Two recent randomized controlled trials in adults on the use of steroids in suspected adrenal insufficiency showed conflicting results (12,13), further adding to the controversy. We identified only a few small observational studies (ranging from 13-72 patients; see Table E1 in the online supplement) examining adrenal insufficiency in pediatric critical illness (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24). These pediatric studies used multiple different definitions for the diagnosis of adrenal insufficiency, focused almost exclusively on patients with septic shock (17,19,20,22,23), did not conduct corticotropin stimulation tests on all patients (only obtained random cortisol levels) (15,16,24), and used different doses for the corticotropin tests.…”
Section: Abstract Adrenal Gland; Adrenal Function; Adrenocorticotropimentioning
confidence: 99%
“…We identified only a few small observational studies (ranging from 13-72 patients; see Table E1 in the online supplement) examining adrenal insufficiency in pediatric critical illness (14-24). These pediatric studies used multiple different definitions for the diagnosis of adrenal insufficiency, focused almost exclusively on patients with septic shock (17,19,20,22,23), did not conduct corticotropin stimulation tests on all patients (only obtained random cortisol levels) (15,16,24), and used different doses for the corticotropin tests. As a result, the reported prevalence of adrenal insufficiency varies from 10 (16) to 100% (15).…”
Section: Abstract Adrenal Gland; Adrenal Function; Adrenocorticotropimentioning
confidence: 99%
“…Therefore, such frequent variations in the cortisol concentration make the ACTH tests inaccurate because they rely on a just few time-point measurements that can be taken either at the peak or trough of the pulse [40]. Several studies tried to assess the HPA axis during surgery [41][42][43][44][45][46][47][48][49][50][51]. Some used a few time cortisol measurements or just ACTH stimulation tests and tried to correlate their findings with clinical outcomes.…”
Section: Steroids and The Hypothalamic-pituitary-adrenal Axismentioning
confidence: 99%